Effects of naloxone distribution alone or in combination with addiction treatment with or without pre-exposure prophylaxis for HIV prevention in people who inject drugs: a cost-effectiveness modelling study. (March 2017) - Uyei, Jennifer; Fiellin, David A; Buchelli, Marianne; Rodriguez-Santana, Ramon; Braithwaite, R Scott
Summary: Background: In the USA, an epidemic of opioid overdose deaths is occurring, many of which are from heroin. Combining naloxone distribution with linkage to addiction treatment or pre-exposure prophylaxis (PrEP) for HIV prevention through syringe service programmes has the potential to save lives and be cost-effective. We estimated the outcomes and cost-effectiveness of five alternative strategies: no additional intervention, naloxone distribution, naloxone distribution plus linkage to addiction treatment, naloxone distribution plus PrEP, and naloxone distribution plus linkage to addiction treatment and PrEP. Methods: We developed a decision analytical Markov model to simulate opioid overdose, HIV incidence, overdose-related deaths, and HIV-related deaths in people who inject drugs in Connecticut, USA. Model input parameters were derived from published sources. We compared each strategy with no intervention, as well as simultaneously considering all strategies. Sensitivity analysis was done for all variables. Linkage to addiction treatment was referral to an opioid treatment programme for methadone. Endpoints were survival, life expectancy, quality-adjusted life-years (QALYs), number and percentage of overdose deaths averted, number of HIV-related deaths averted, total costs (in 2015 US$) associated with each strategy, and incremental cost per QALY gained. Findings: In the base-case analysis, compared with no additional intervention, the naloxone distribution strategy yielded an incremental cost-effectiveness ratio (ICER) of $323 per QALY, and naloxone distribution plus linkage to addiction treatment was cost saving compared with no additional intervention (greater effectiveness and less expensive). The most efficient strategies (ie, those conferring the greatest health benefit for a particular budget) were naloxone distribution combined with linkage to addiction treatment (cost saving), and naloxone distribution combined with PrEP and linkage to addiction treatment (ICER $95 337 per QALY) at a willingness-to-pay threshold of $100 000. In probabilistic sensitivity analysis, the combination of naloxone distribution, PrEP, and linkage to addiction treatment was the optimal strategy in 37% of iterations and the combination of naloxone distribution and linkage to addiction treatment was the optimal strategy in 34% of iterations. Interpretation: Naloxone distribution through syringe service programmes is cost-effective compared with syringe distribution alone, but when combined with linkage to addiction treatment is cost saving compared with no additional services. A strategy that combines naloxone distribution, PrEP, and linkage to addiction treatment results in greater health benefits in people who inject drugs and is also cost-effective. Funding: State of Connecticut Department of Public Health and the National Institute of Mental Health.